Lambda Calculus Conversion

How can I take a data type or function (eg fold, list, String, zip) and convert it to a lambda calculus expression (or how can it be expressed as a lambda expression)?
If sum computes a sum of all elements in a list and :t sum -> Num a => [a] -> a. How do I take this information to translate it to a lambda calculus expression? I have tried to find guides online but they just give me the answers. I want to know how to actually make the conversion/translation from a function to a lambda calculus expression.